Correlation of Haemoglobin Platelet Ratio (HPR) and LeukocytePlatelet Ratio (LPR) with SYNTAX-2 Score in STEMI Patients - Ikhsan, Muhammad; Nasution, Sally Aman; Rachman, Andhika; Muhadi, Muhadi (Jurnal Penyakit Dalam Indonesia, 2021)
Introduction. Various studies have concluded the association between various markers of inflammation with the clinical outcome in STEMI patients. However, most of these markers are quite expensive and not available in healthcare facilities. Hence, we aim to study the correlation between haemoglobin platelet ratio (HPR) and leucocyte platelet ratio (RPL) and the clinical outcomes of STEMI patients. Methods. This is a cross-sectional study performed in adult patients with STEMI who were hospitalized in Intensive Coronary Care Unit Cipto Mangunkusumo Hospital between January 2016 and October 2020. The data was analyzed by testing the correlation between HPR and LPR with SYNTAX-2 score. Results. There were 114 subjects in this study, with a mean age was 53.87 years and dominated by male (86.8%). We found no correlation between HPR and LPR with SYNTAX-2 Score. From the sub-group analysis, there was a moderate positive correlation between HPR and SYNTAX-2 score (r = 0.587; p= 0.005) and a strong positive correlation between LPR and SYNTAX-2 score (r = 0.606; p = 0.004) in subjects with normal body mass index (BMI). Additional results obtained a strong negative correlation between neutrophil lymphocyte ratio (NLR) with SYNTAX-2 score (r = -0.738; p= 0.0037) and a very strong negative correlation between platelet lymphocyte ratio (PLR) with SYNTAX-2 score (r= -0,857; p= 0,007) in subjects with low BMI. Conclusion. There is no correlation between HPR and LPR with SYNTAX-2 Score